Rousseau vivant: en aktualisering af Émile med fokus på det lidenskabelige fænomenfelt - Thøgersen, Ulla (Studier i Pædagogisk Filosofi, 2013)
The paper focuses on Rousseau’s understanding of passionate life and especially his interpretation of erotic desire in Émile. The main argument presented is that Rousseau by his studies of erotic desire gives us at present day the possibility of radicalizing our understanding of human being in pedagogy. Firstly, by allowing us to rethink passions as important phenomena in human life and secondly, by understanding pedagogical practice as an arena which is part of forming passions, including erotic desire.